(untitled) (Educação e Pesquisa, 2021)
This erratum corrects the article English language assessment: unfolding school students’ and parents’ views DOI: 10.1590/S1678-4634202147226529 published in Educação e Pesquisa, v. 47, p. 01-25, e-location e226529, 2021.